Buzzing Sympathetic Nerves: A New Test to Enhance Anisocoria in Horner's Syndrome - Omary, Rawan; Bockisch, Christopher J.; Landau, Klara; Kardon, Randy H.; Weber, Konrad P. (Frontiers in Neurology, 2019)
Introduction: Patients with suspected Horner's syndrome having equivocal pupil dilation lag and pharmacologic testing may undergo unnecessary MR imaging and work up in the case of false positive pupil test results. Our goal was to increase the diagnostic accuracy of pupillometry by accentuating the inter-ocular asymmetry of sympathetic innervation to the iris dilator with surface electrical stimulation of the median nerve using a standard electromyography machine. We hypothesized that an accentuated difference in sympathetic response between the two eyes would facilitate the diagnosis of Horner's syndrome. Methods: Eighteen patients with pharmacologically proven Horner's syndrome were compared to ten healthy volunteers tested before and after monocular instillation of 0.2% brimonidine tartrate ophthalmic solution to induce pharmacological Horner's syndrome. Pupillary responses were measured with binocular pupillometry in response to sympathetic activation by electrical stimulation of the median nerve in darkness and at various times after extinction of a light stimulus. Sudomotor sympathetic responses from the palm of the stimulated arm were recorded simultaneously. Results: In subjects with Horner's syndrome and pharmacologically induced unilateral sympathetic deficit, electrical stimulation in combination with the extinction of light greatly enhanced the anisocoria during the evoked pupil dilation, while there was no significant increase in anisocoria in healthy subjects. The asymmetry of the sympathetic response was greatest when the electrical stimulus was given 2 s after termination of the light or under constant low light conditions. When given 2 s after termination of light, the electrical stimulation increased the mean anisocoria from 1.0 to 1.2 mm in Horner's syndrome (p = 0.01) compared to 0.22–0.26 mm in healthy subjects (p = 0.1). In all subjects, the maximal anisocoria induced by the electrical stimulation appeared within a 2 s interval after the stimulus. Correspondingly, the largest change in anisocoria between light and dark without electrical stimulation was seen between 3 and 4 s after light-off. While stronger triple stimulation further enhanced the anisocoria, it was less well tolerated. Conclusions: Electrical stimulation 2 s after light-off greatly enhances the sensitivity of pupillometry for diagnosing Horner's syndrome. This new method may help to rule in or rule out a questionable Horner's syndrome, especially if the results of topical pharmacological testing are inconclusive.